Yahoo Answers: Answers and Comments for Find the difference quotient of f; that is,
find f(x+h)f(x) / h ,h ≠ 0 .
Be sure to simplify.? [Mathematics]
Copyright © Yahoo! Inc. All rights reserved.
https://in.answers.yahoo.com/question/index?qid=20200120002920AA0Dt1i
From Anonymous
enIN
Mon, 20 Jan 2020 00:29:20 +0000
3
Yahoo Answers: Answers and Comments for Find the difference quotient of f; that is,
find f(x+h)f(x) / h ,h ≠ 0 .
Be sure to simplify.? [Mathematics]
292
38
https://in.answers.yahoo.com/question/index?qid=20200120002920AA0Dt1i
https://s.yimg.com/zz/combo?images/emaillogoin.png

From ?: See below for work and answer:
https://in.answers.yahoo.com/question/index?qid=20200120002920AA0Dt1i
https://in.answers.yahoo.com/question/index?qid=20200120002920AA0Dt1i
Mon, 20 Jan 2020 02:16:15 +0000
See below for work and answer:

From llaffer: You have:
f(x) = x²  9x + 2
And asked to so...
https://in.answers.yahoo.com/question/index?qid=20200120002920AA0Dt1i
https://in.answers.yahoo.com/question/index?qid=20200120002920AA0Dt1i
Mon, 20 Jan 2020 01:27:16 +0000
You have:
f(x) = x²  9x + 2
And asked to solve for:
[f(x + h)  f(x)] / h
We have f(x) already, so we need to find f(x + h):
f(x) = x²  9x + 2
f(x + h) = (x + h)²  9(x + h) + 2
Simplify:
f(x + h) = x² + 2hx + h²  9x  9h + 2
Now we can substitute both expressions into the main expression and simplify:
[f(x + h)  f(x)] / h
[(x² + 2hx + h²  9x  9h + 2)  (x²  9x + 2)] / h
(x² + 2hx + h²  9x  9h + 2  x² + 9x  2) / h
Cancel out what can be:
(2hx + h²  9h) / h
Factor out the h and cancel with the denominator:
h(2x + h  9) / h
2x + h  9

From az_lender: Ted was doing well until he (mis)typed 2x  6 ...
https://in.answers.yahoo.com/question/index?qid=20200120002920AA0Dt1i
https://in.answers.yahoo.com/question/index?qid=20200120002920AA0Dt1i
Mon, 20 Jan 2020 00:42:22 +0000
Ted was doing well until he (mis)typed 2x  6 + h.
He meant 2x  9 + h.

From ted s: ( x + h)²  x²  ( 9x + 9h  9 x ) + ( 2  2 )...
https://in.answers.yahoo.com/question/index?qid=20200120002920AA0Dt1i
https://in.answers.yahoo.com/question/index?qid=20200120002920AA0Dt1i
Mon, 20 Jan 2020 00:32:49 +0000
( x + h)²  x²  ( 9x + 9h  9 x ) + ( 2  2 ) = 2 h x + h²  9 h = h [ 2x + h  9 ] ===> answer is 2x  6 + h